Acetylcholinesterase‐Catalyzed Hydrolysis Allows Ultrasensitive Detection of Pathogens with the Naked Eye1. Issue 52 (23rd October 2013) - Liu, Dingbin; Wang, Zhantong; Jin, Albert; Huang, Xinglu; Sun, Xiaolian; Wang, Fu; Yan, Qiang; Ge, Shengxiang; Xia, Ningshao; Niu, Gang; Liu, Gang; Hight Walker, A. R.; et al.
<x xml:space="preserve">Abstract</x> Seeing is believing: A rapid diagnostic platform for pathogen detection based on the acetylcholinesterase‐catalyzed hydrolysis reaction has been developed. Owing to signal amplification strategies, the sensitivity of this assay is comparable to that of PCR. In addition, the readout of the assay is based on solution color change, which can be easily observed by the naked eye alone.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>